The economics of trade protection - Vousden, Neil 1947- (Cambridge University Press, 1990)
Over the past two decades there has been a gradual but fundamental change in the nature of trade protection. Even as international negotiation has succeeded in reducing tariffs to low levels, national governments have resorted to a range of increasingly intricate policies to protect their domestic industries from foreign competition. Direct quantitative restrictions on international trade have become particularly widespread. Such nontariff barriers often have very different effects from tariffs and require careful analysis in their own right. This book presents a systematic overview of the modern theory of trade protection. The material in the book divides naturally into four sections. The first section covers trade restrictions in competitive markets, the second trade restrictions and imperfect competition, the third the political economy of trade protection, and the fourth the theory of policy reform. The presentation makes extensive use of diagrams, with the more difficult mathematics included in six appendixes. This approach emphasises microeconomics and makes the book suitable for graduate and advanced undergraduate students in the social sciences who have taken one intermediate microeconomics course